Analysis of the Effectiveness of Halal Tourism Fatwas: A Study on Awareness, Implementation, and Impact in the Tourism Industry - Rahmatullah; Abdul Mujib (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: This research aims to analyze the effectiveness of DSN-MUI Fatwa No. 108/DSN-MUI/X/2016 as a guideline for organizing tourism based on sharia principles, emphasizing three dimensions: (i) awareness among stakeholders, (ii) implementation in destination/industry practices, and (iii) economic and social impacts within the tourism industry. The analysis is situated within the context of Indonesia’s halal industry ecosystem, where halal certification is often understood as an instrument for enhancing consumer trust and competitive advantage, including in the tourism and culinary sectors. The research questions include: (1) to what extent is stakeholder awareness of fatwas and halal tourism indicators established; (2) what are the patterns of implementation and the barriers to implementation; and (3) what are the observed impacts on well-being, destination performance, and public acceptance. Method: The research method employs a qualitative-descriptive literature review based on thematic synthesis of empirical/conceptual studies related to fatwas, derivative regulations, halal certification, marketing, financing, and case studies of destination implementation across various regions. Results: The synthesis results indicate that the effectiveness of fatwas is uneven: fatwas generally function as normative references and ethical-service standards; however, the effectiveness of their implementation is influenced by the strength of positive regulations, institutional capacity, halal literacy/education, facility readiness, and social acceptance within the context of a diverse society. Conclusion: The study’s implications emphasize the need to strengthen governance (stakeholder collaboration), performance measurement based on indices/indicators, and education-communication strategies so that fatwa guidelines can be more operational and have a sustainable impact.